Pengaruh Tax Avoidance, Agency Cost Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Kepemilikan Institutional Sebagai Variabel Moderasi - Wulandari, Hana Dwi; Ratnasari, Fina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Firm value is a crucial indicator for investors as it reflects both the company’s performance and long-term competitiveness. Prior studies on the effects of tax avoidance, agency cost, and capital structure on firm value have shown inconsistent results, particularly regarding the role of institutional ownership in moderating these relationships. This study aims to examine the effect of tax avoidance, agency cost, and capital structure on firm value with institutional ownership as a moderating variable. The research uses a quantitative approach with panel data from 21 food and beverage companies listed on the Indonesia Stock Exchange during 2020-2023, resulting in 84 firm-year observations. Data were analyzed using panel regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA) assisted by EViews 13. The findings indicate that simultaneously, tax avoidance, agency cost, and capital structure affect firm value. Partially, tax avoidance and agency cost do not significantly influence firm value, while capital structure has a positive effect. Furthermore, institutional ownership strengthens the moderating effect on the relationship between tax avoidance and capital structure with firm value, but fails to moderate agency cost. These results highlight the importance of institutional ownership in enhancing governance and sustaining firm value in the consumer non-cyclical sector.